2020
DOI: 10.1159/000499252
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Ability for Disease-Free Survival of the GRade, Age, Nodes, and Tumor (GRANT) Score in Patients with Resected Renal Cell Carcinoma

Abstract: Background: Recently, the GRANT (GRade, Age, Nodes, and Tumor) score was validated through an adjuvant trial population. Methods: This retrospective study evaluated the performance of the GRANT score as a prognostic model for disease-free survival (DFS), compared to the University of California Los Angeles Integrated Staging System (UISS) score, in a “real-life” population of early renal cell carcinoma patients. A uni-/multivariate analysis of DFS was also performed, to weigh the roles of baseline clinical fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…We found increasing age, size of the tumor, histologic grade, stage, and presence of necrosis to be associated with significantly decreased survival among our cases on univariate cox regression. Gudbjartsson et al, Lamb et al and Cortellini et al also found a similar trend in their case series with respect to age, size, grade, and stage of the tumor as depicted in Table 5 ( 1 , 14 , 15 ). There was no statistically significant difference among the various histologic subtypes.…”
Section: Discussionsupporting
confidence: 70%
“…We found increasing age, size of the tumor, histologic grade, stage, and presence of necrosis to be associated with significantly decreased survival among our cases on univariate cox regression. Gudbjartsson et al, Lamb et al and Cortellini et al also found a similar trend in their case series with respect to age, size, grade, and stage of the tumor as depicted in Table 5 ( 1 , 14 , 15 ). There was no statistically significant difference among the various histologic subtypes.…”
Section: Discussionsupporting
confidence: 70%
“…Several prognostic models incorporating clinical and pathological RCC variables have been validated to predict recurrence and mortality after nephrectomy in chRCC [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Of these, two models are recommended by European guidelines to predict cancer control outcomes after nephrectomy in non-metastatic chRCC [ 15 ]: Leibovich 2018 [ 2 , 16 ] and GRade, Age, Nodes and Tumor (GRANT) [ 3 , 16 , 17 , 18 , 19 , 20 ]. However, their ability to predict cancer-specific survival (CSS) has only been validated in a mono-institutional European cohort of 127 chRCC patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…10 The score is easy to use and has been validated. 11,12 The GRANT score was based on patient age, and pathologic features; Fuhrman grade, nodal status (pN) and tumor size (pT). GRANT has demonstrated excellent discrimination for predicting recurrence in both ccRCC and non-ccRCC patients and may therefore be an acceptable and simpler alternative to the Leibovich score.…”
Section: Introductionmentioning
confidence: 99%
“…A new risk stratification tool for RCC was recently developed: the GRANT score 10 . The score is easy to use and has been validated 11,12 . The GRANT score was based on patient age, and pathologic features; Fuhrman grade, nodal status (pN) and tumor size (pT).…”
Section: Introductionmentioning
confidence: 99%